2005
DOI: 10.1097/01.ju.0000173078.57871.2d
|View full text |Cite
|
Sign up to set email alerts
|

PROGNOSTIC ROLE OF FUHRMAN GRADE AND VASCULAR ENDOTHELIAL GROWTH FACTOR IN pT1a CLEAR CELL CARCINOMA IN PARTIAL NEPHRECTOMY SPECIMENS

Abstract: Our study shows that recurrence and death are possible even in patients with small renal tumors. MVD, VEGF and Flk-1 expression do not depend on tumor size in pT1a RCC. Therefore, to date Fuhrman grading appears to be the only factor predictive of survival even in small RCC. Thus, Fuhrman grading is predictive of mortality. While VEGF is not predictive of survival as a single parameter, based on its percent of expression (lower or higher than 25%) it can determine 2 groups that are different from the prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 18 publications
2
55
2
1
Order By: Relevance
“…Four (8.3%) developed metastatic disease at 24 months. 29 The majority of series that report metastatic disease indicate that there was interval growth in the primary lesion and that most tumors displayed an accelerated growth rate. 7,14,21,23,30,31,32 Therefore, an increased growth rate may be associated with progression to metastatic disease.…”
Section: Outcomes After Long-term Follow-upmentioning
confidence: 99%
“…Four (8.3%) developed metastatic disease at 24 months. 29 The majority of series that report metastatic disease indicate that there was interval growth in the primary lesion and that most tumors displayed an accelerated growth rate. 7,14,21,23,30,31,32 Therefore, an increased growth rate may be associated with progression to metastatic disease.…”
Section: Outcomes After Long-term Follow-upmentioning
confidence: 99%
“…4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation. However, one other important cause may be that, without differential analysis, blood vessels in CCRCC may be regarded as a single type of vessel having presumably similar functions throughout, which might not accurately reflect the functional diversity of different types of microvessels.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 99%
“…remaining 42 articles were reviewed, and of these 23 were excluded, the reasons for which are shown in Figure 1. Thus, 19 studies were included in the quantitative synthesis [10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Five of these studies [20,22,25,33,36] did not provide data (HR or Kaplan-Meier curve) to calculate the HR for OS, PFS, or DSS, and therefore could not be included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the four studies that provided tumor VEGF expression data [27,29,31,35] indicated that high VEGF expression was associated with worse DSS (pooled HR = 1.83; 95% CI: 1.24 to 2.71; p = 0.003, Figure 2B). …”
Section: Vegf Tumor Expressionmentioning
confidence: 99%